Design and analysis of cooling loads in freezers based on phase change materials - Boni Sena; Hadi Nurwahyudin; Kahfi Alwi Kasim; Ksatria Danuaji; Raflihuda Dwi Agusti; Faishal Dzaky Al Hakim; Ribka Bernaditta Naibaho; Nadia Amanah; Fardin Hasibuan (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
Improving energy efficiency and temperature stability in freezer systems is a critical issue due to high energy consumption and thermal fluctuations that can degrade the quality of frozen products. Previous research has generally focused on compressor optimization and active refrigeration systems, while the use of Phase Change Materials (PCMs) as passive energy storage media in small-scale freezers is still limited. This study aims to analyze the effect of adding PCMs on the cooling load and thermal performance of the freezer. The methods used include designing a three-layer wall model (aluminum–polyurethane–PCM), calculating conduction energy, sensible heat, and latent heat, and comparing seven types of PCMs using an analytical approach and CoolTools-based thermal simulation. The results show that dry ice gel provides the best performance with the lowest total cooling load of 29.02 W and latent heat of 5.40 × 10⁵ J/kg. The system has a COP of 2.36 with a thermodynamic efficiency of 53.74%. PCM integration has been proven to reduce temperature fluctuations and reduce system workload, thus contributing scientifically to the development of energy-efficient freezer designs based on passive thermal energy storage.